Reduction of boundary value problems to difference and differential-difference equations - Klevchuk, I.I. (Yuriy Fedkovych Chernivtsi National University, 2003)
We reduce boundary value problems for hyperbolic systems of differential equations to difference and differential-difference equations. We construct the domain of stability for a linear autonomous differential equation with two delays.
We reduce boundary value problems for hyperbolic systems of differential equations to difference and differential-difference equations. We construct the domain of stability for a linear autonomous differential equation with two delays.
Keywords: differential-difference equation; difference equation; boundary value problem; hyperbolic differential equation